(untitled) (Research, Society and Development, 2023)
The pandemic caused by COVID-19 caused several individual and social damages because it is an atypical and unknown disease. In health systems, it triggers cumulative effects for professionals in the area and users of services. This study shares the data found and analyzes the mental health of professionals at the Basic Health Unit in the city of Lagarto-SE in terms of lifestyle, emotional, stress and mood. Data collection and their respective graphs were taken from the instruments, adapted from instruments, formulated on the Google Forms platform. Results demonstrate damage to the psychological well-being of professionals during the pandemic, both in self-perception (76.9%) and diagnosis (46.2%). It is concluded that although the article does not have a high percentage regarding the mental overload of health professionals, in opposition to other research, it is necessary to carry out new scientific research and programs aimed at the mental health of professionals.